Nurse competence in using the Glasgow Coma Scale in the emergency installation room of hospital - Waluyo, Endrian Mulayady; Kusumawaty, Jajuk; Nurapandi, Adi (Universitas Aisyah Pringsewu, 2020)
The Glasgow Coma Scale technique is used by nurses and health care professionals to facilitate assessment documentation of the consciousness scale. A consciousness assessment needed in patients with neurological problems and injuries. The Glasgow Coma Scale is also needed to determine clinical decisions in the hospital emergency unit. The purpose of this study is to assess the nurses' ability in the Emergency Installation room who already have an emergency training certificate and to analyze the factors that influence the emergency nurses' competence about the Glasgow Coma Scale at the Emergency Installation room of Government General Hospital. The method used is descriptive-analytic with the chi-square relationship test approach and the samples were taken based on total sampling, namely all nurses in Emergency Installation as many as 73 people spread across three hospitals in West Java. The sample has nurses' inclusion criteria who have emergency department training certificates and served in the Emergency Installation. Exclusion criteria were nurses who served structurally (head of the room and deputy head of the room) and were not on duty. The results showed that nurse competence was influenced by nurses' age and years of service. In conclusion, the Glasgow Coma Scale instrument has an important role in the emergency room so, it needed the same benchmarks between the hospital and the training which was followed by nurses. The recommendations based on this research are the need for standard benchmarks and modification of the Glasgow Coma Scale Instrument to make it easier to use and remain accurate as a predictor of death. Kompetensi perawat dalam menggunakan Glasgow Coma Scale di ruang instalasi darurat rumah sakitAbstrak: Teknik Glasgow Coma Scale digunakan oleh perawat dan tenaga medis kesehatan untuk memudahkan pendokumentasian penilaian skala kesadaran, penilaian kesadaran dibutuhkan pada pasien permasalahan neurologis dan cedera. Glasgow Coma Scale juga diperlukan untuk menentukan keputusan klinis pada unit gawat darurat di rumah sakit. Tujuan dari penelitian, yaitu menilai kemampuan perawat di ruangan Instalsi Gawat Darurat yang sudah memiliki sertifikat pelatihan gawat darurat dan menganalisa faktor-faktor yang mempengaruhi kompetensi perawat gawat darurat tentang Glasgow Coma Scale di Instalasi Gawat Darurat Rumah Sakit Umum Pemerintah. Metode yang digunakan adalah deskriptif analitik dengan pendekatan uji hubungan chi square dengan sampel diambil berdasarkan total sampling yaitu seluruh perawat Instalsi Gawat Darurat sebanyak 73 orang yang tersebar di tiga rumah sakit di Jawa Barat. Sampel memiliki kriteria inklusi perawat yang memiliki sertifikat pelatihan gawat darurat dan bertugas di Instalsi Gawat Darurat Kriteria eksklusi yaitu perawat yang menjabat struktural (kepala ruangan dan wakil kepala ruangan) dan sedang tidak bertugas. Hasil penelitian menunjukan bahwa kompetensi perawat dipengaruhi oleh usia dan masa kerja perawat. Kesimpulan instrument Glasgow Coma Scale memiliki peranan penting di ruang unit gawat darurat sehingga di perlukan tolak ukur yang sama antara rumah sakit dan pelatihan yang di ikuti oleh perawat. Rekomendasi berdasarkan penelitian ini yaitu perlu tolak ukur yang baku dan modifikasi Instrument Glasgow Coma Scale agar lebih mudah di gunakan dan tetap akurat sebagai prediktor kematian.